Dermal tunneling: a proposed treatment for depressed scars - Emerson Vasconcelos de Andrade Lima (Sociedade Brasileira de Dermatologia, 2016)
Abstract: Depressed facial scars are still a challenge in medical literature, despite the wide range of proposed treatments. Subcision is a technique that is frequently performed to improve this type of lesions. This article proposes a new method to release depressed scars, reported and named by the author as dermal tunneling. This study presents a simple and didactic manner to perform this method. The results in 17 patients with facial scars were considered promising. Thus, the technique was deemed to be safe and reproducible.